Perfil dos ácidos graxos em espécies de microalgas de água doce da família Selenastraceae (Chlorophyta) como característica quimiotaxonômica e prospecção de aplicabilidade - Mori, Cilene Cristina (Universidade Federal de São Carlos, 2016)
The identification Selenastraceae family organism is performed by optical microscopy only on diacritic characteristics, what has been questioned from recent molecular studies. Conflicts between phylogenetic, morphologic and genetic results were found after analysis of a large number of species Selenastraceae, and misidentification and consequently error in the classification directly leads to that the underestimation of species from Selenastraceae family. An alternative to these errors in identification and classification would be avoided using a polyphasic taxonomic approach to this family, combining to morphology, genetics, physiology and chemotaxonomy. Therefore, the use of fatty acids found in microalgae as an alternative to contribute assist in identification can be feasible. Using this information, this study considered the fatty acids of sixteen strains of microalgae from Selenastraceae family and found specific fatty acids and may differentiate between strains of microalgae and has presented fatty acids indicators from the Selenastraceae families (C18:3ω3 and C18:4ω6), Scenedesmaceae (C18:2ω6, C18:1ω9, C16:2ω6) and Oocystaceae (C18:3ω6) and also genera Monoraphidium (C16:1ω9 and C16:3ω6), Coelastrum (C18:1ω9) and Nephrocytium (C18:3ω6). Among Selenastraceae was detected potential with fatty acids for the production of biofuels (C18:1ω9), to feeding to animals (C16:0) and polyunsaturated for human nutritional supplements (C18:3ω3, C18:2ω6 and C16:4ω3) according the growing stage of these organisms.
Keywords: Microalgas; Água doce; Selenastraceae; CIENCIAS BIOLOGICAS::BIOQUIMICA